Occupational health risk perceptions and determinants: knowledge and attitude of sanitary workers in public hospitals of Ethiopia - Tolera, Sina Temesgen; Gobena, Tesfaye; Geremew, Abraham; Toseva, Elka; Assefa, Nega (Frontiers in Public Health, 2025)
IntroductionOccupational health risks (OHRs) perception refer to an individual’s subjective assessment of the likelihood and severity of potential health hazards within their workplace, which are influenced by their knowledge and attitude. The OHRs perceptions of sanitary workers (SWs) in Ethiopia have not yet been well studied. Therefore, this study aims to assess the knowledge and attitude of SWs about OHR perceptions and their determinants in public hospitals of eastern Ethiopia.MethodsA hospital-based cross-sectional study was conducted on a total of 809 SWs, which comprised face-to-face interviews. Knowledge items were measured by [YES/NO] and then categorized as “good” if they scored 16–20 points; “fair” if 10–15 points; and “poor” if < 10 points. On the other hand, attitude items were measured on Likert scales [strongly disagree (1) to strongly agree (5)] and classified as level 1: unfavorable; level 2: neutral; and level 3: favorable. Stata 17MP version was used for data analysis. The univariate analysis was applied for frequency, prevalence, media, and mean. Multilevel ordinal logistic regression was conducted for the predictions. Structural equation modeling (SEM) was used to determine the correlations between level of knowledge of and attitude toward OHRs perceptions as well as with their predictors.ResultThis study found that the poor level of knowledge of and unfavorable attitude toward OHRs among SWs were 67.35 and 42.66%, respectively. The difference in knowledge of and attitude toward OHRs perceptions of SWs between hospitals was 19.34 and 39.55%, respectively. The final model showed that the variables trained on occupational health and safety [OHS] (AOR: 4.90; 3.10, 7.75), satisfied with job (AOR: 1.88; 1.10, 3.75), and satisfied with environment (AOR: 2.57; 1.09, 6.05) were significantly associated with higher knowledge levels about OHRs. However, SWs who were satisfied with environment (AOR: 2.67; 1.03, 6.92) and who follow good infection prevention and control (IPC) practice (AOR: 20.43; 15, 35.84) were significantly associated with a high level of attitude toward OHRs. SEM results showed that OHS training (β: 0.35; 0.27, 0.44) and compliance with IPC (β: 0.07; 0.02, 0.12), as well as compliance with personal protective equipment (β: 0.14; 0.04, 0.23), had a positive impact on the knowledge and attitude about OHRs.ConclusionThis study concluded that the majority of SWs had inadequate knowledge about and negative attitude toward OHRs perceptions. The following variables played the most significant role in predicting the SWs’ knowledge of and attitude toward OHRs: OHS training, job and environmental satisfaction, safety measures, and job stress, which could be considered for further interventions.